Edukasi Geodiversitas Kaldera Ijen Purba Berbasis Pembelajaran Lapangan bagi Generasi Muda dalam Mendukung Ijen UNESCO Global Geopark - Muhammad Asyroful Mujib; Tri Rafika Diyah Indartin; Bejo Apriyanto; Unggul Widyanarko (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Low geodiversity literacy has led the Ijen area to be widely perceived as a natural tourism destination rather than as a geoheritage system with scientific, educational, conservation, and social values. This community service program aimed to improve geodiversity literacy, understanding of the functions of the Ijen UNESCO Global Geopark, and awareness of conservation and sustainable tourism among young people. The program was implemented through a field-based participatory educational approach using experiential learning principles over three days and two nights in the Ancient Ijen Caldera. A total of 50 participants were involved, consisting of senior high school students, undergraduate students, master’s students, and young teachers. The activities included orientation sessions, mini-lectures, geosite observations, field interpretation, group discussions, reflection, and evaluation at four main geosites: Kawah Wurung, Kalipait, Plalangan Black Lava, and Kawah Ijen. The results showed that participants were able to understand the interconnections among geosites, distinguish ordinary nature-based tourism from geotourism based on geological interpretation, and recognize the importance of geoconservation. The average post-test score reached 79 out of 100, with scores of 82 for regional geosite values, 80 for geoconservation and sustainable tourism, 79 for geopark functions, and 75 for geoheritage. The lower score for geoheritage indicates that understanding of geological heritage values still requires stronger interpretation and continuous assistance. Therefore, field-based geodiversity education represents an effective strategy for enhancing geoscience literacy, fostering conservation awareness, and empowering young people to support the long-term sustainability of the Ijen UNESCO Global Geopark.